Increased lymphocyte apoptosis in mouse models of colitis upon ABT-737 treatment is dependent upon BIM expression. (19th May 2015) - Lutz, C; Mozaffari, M; Tosevski, V; Caj, M; Cippà, P; McRae, B L; Graff, C L; Rogler, G; Fried, M; Hausmann, M
Summary: Exaggerated activation of lymphocytes contributes to the pathogenesis of inflammatory bowel disease (IBD). Medical therapies are linked to the BCL-2 family-mediated apoptosis. Imbalance in BCL-2 family proteins may cause failure in therapeutic responses. We investigated the role of BCL-2 inhibitor ABT-737 for lymphocyte apoptosis in mice under inflammatory conditions. B.6129P2-interleukin (IL)-10 tm1Cgn /J ( IL-10 −/− ) weighing 25–30 g with ongoing colitis were used. Fifty mg/kg/day ABT-737 was injected intraperitoneally (i.p.). Haematological analyses were performed with an ADVIA 2120 flow cytometer and mass cytometry with a CyTOF 2. Following i.p. administration, ABT-737 was detected in both spontaneous and acute colitis in peripheral blood (PBL) and colon tissue. Treatment led to lymphopenia. CD4 + CD44 + CD62L + central memory and CD8 +, CD44 + CD62L − central memory T cells were decreased in PBL upon ABT-737 compared to vehicle-receiving controls. Increased apoptosis upon ABT-737 was determined in blood lymphocytes, splenocytes and Peyer's patches and was accompanied by a decrease in TNF and IL-1B . ABT-737 positively altered the colonic mucosa and ameliorated inflammation, as shown by colonoscopy, histology and colon length. A decreased BIM / BCL-2 ratio or absence of BIM in both Bim − / − and Il10 − / − × Bim − / − impeded the protective effect of ABT-737. The BIM / BCL-2 ratio decreased with age and during the course of treatment. Thus, long-term treatment resulted in adapted TNF levels and macroscopic mucosal damage. ABT-737 was efficacious in diminishing lymphocytes and ameliorating colitis in a BIM-dependent manner. Regulation of inappropriate survival of lymphocytes by ABT-737 may provide a therapeutic strategy in IBD.